Respuesta :

r3t40
Hi,


WORK:

[tex] \frac{1}{3} \times (r + 6) = \frac{1}{6} \times (r + 8) \\ [/tex]

Multiply both sides of equation by 3.

[tex]r + 6 = \frac{1}{2} \times (r + 8)[/tex]

Distribute one half thought parenthesis.

[tex]r + 6 = \frac{1}{2} \times r + 4[/tex]

Multiply both sides of equation by 2.

[tex]2r + 12 = r + 8[/tex]

Move r variable to left side and change its sign.

[tex]2r - r + 12 = 8[/tex]

Collect the like terms.

[tex]r = 8 - 12[/tex]

Result:

[tex]r = - 4[/tex]

Hope this helps.
r3t40